MAGICAL REALISM IN THE COMPARATIVE CONTEXT (Filološke studije, 2019)
This paper considers to what extent contemporary discourses about magical realism might contribute to a comparative understanding of the works of Milorad Pavić, especially his novel Dictionary of the Khazars. Comparative analysis of elements of magical realism in Pavić’s exemplary novel reveals characteristics of both European and Latin American forms of magical realism. Therefore, the paper places Pavić’s novel into the context of magical realism.